HISTORICAL DEVELOPMENT OF UZBEK MILITARY TERMINOLOGY (Journal of Pharmaceutical Negative Results, 2022)
The article is about the history of formation of Uzbek military terminology, the problems of its translation and the process of regulating and unification of the military terminology. As all the other languages the Uzbek military terminology also has its own specific way of development, which has a way back long history dating back to the primitive times, when the military terminology started its formation already, by man naming the primitive weapons and tactics used when hunting food or defending from enemies. In the following centuries, some other languages have influenced the Uzbek military terminology forming the terminology which had some imperfections as well. Due to the fast development of mass media the new term (neologism), which appeared in one specific language couldn’t stay inside that language for a long time. It is typical, especially for the military terms. And here comes the art of translation which faced the problems of transferring clearly the term into the other language. Because the Uzbek terminology of the early XXth century needed to be sorted out and regulated properly.